2018
DOI: 10.2340/00015555-2924
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome Activation Characterizes Lesional Skin of Folliculitis Decalvans

Abstract: Folliculitis decalvans (FD) is a chronic inflammatory disease leading to scarring alopecia with poorly defined pathogenesis. The aim of this study was to investigate the expression of markers associated with the activation of innate immune signals, such as inflammasome (NALP1 and NALP3), interleukin (IL)-1β and IL-8 and type I interferon (MxA). A retrospective monocentric study was conducted and included 17 patients with FD with available biopsies. Disease activity (stable vs. active) was defined clinically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…The clinical response was considered good to excellent when an FD-IGA score ≤ 2 was obtained. This cut-off corresponds to the absence of pustules and/or crusts, which are considered the classical signs of disease activity ( 5 , 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical response was considered good to excellent when an FD-IGA score ≤ 2 was obtained. This cut-off corresponds to the absence of pustules and/or crusts, which are considered the classical signs of disease activity ( 5 , 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…This follicular dysbiosis could result from a break in the epidermal barrier, leading to subepidermal colonization by Staphylococcus aureus ( 4 ). Recently, we found involvement of the innate immune response in FD through the inflammasome and interleukin (IL)-1β signalling pathway ( 5 ). Other studies suggest that the Th17 immune response is involved in FD ( 3 ), associated with local expression of pro-inflammatory mediators, such as TNFα ( 6 ).…”
mentioning
confidence: 99%
“…Gradually, fibroblast growth factor and transforming growth factor beta also become upregulated and are thought to mediate the scarring reaction. [3][4][5] Apremilast, as a specific phosphodiesterase 4 inhibitor, suppresses innate and adaptive immune cells, including neutrophils and T cells. Reduced generation of spontaneous reactive oxygen species and of neutrophilic extracellular traps was observed in rheumatoid arthritis patients treated with apremilast.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that the expression of IL-1b was upregulated in both LPP and FD, and the expression of type I IFN-inducible antiviral protein, myxovirus-resistance protein A, was also upregulated in LPP compared with healthy controls. 12 However, abundance of IL-1b and IFN-a is not specific in skin inflammation of LPP and FD, because IL-1b is a common inflammatory cytokine and IFN-a is primarily produced by the plasmacytoid dendritic cells which are common in the inflamed skin. Thus, it may be difficult to attribute the cause of downregulation of ITG-avb6 in LPP and FD scar and subsequent LC loss only to the effect of IL-1b and IFN-a.…”
Section: Discussionmentioning
confidence: 99%